Termografia quantitativa como ferramenta de gestão de ativos do sistema elétrico de potência - Henrique Eduardo Pinto Diniz (2013)
Disregarding the metrological aspects and treating of thermographic inspections of power systems in a merely qualitative manner have led to conservative or ineffective decision making, not complying with the Asset Management principles. In order to apply such principles, in this work a method is developed to estimate the time an electrical joint may break due to loss of the tensile strength of the associated conductor, using thermography as a tool, so no power outages are needed. Therefore, based on the determination of the electrical contact resistance from the inspections results, uncertainty considerations and using estimates of the power loading that will occur in the future, specific models for assessing the damaging effects of this high temperature operation were used to develop an asset management strategy to address the technical risk and economic risk of a joint failure. Results showed that the failure mode evaluated, "joint breakdown", only occurs after a long time of high temperature operation due to annealing, indicating it is dominated by other modes, for example, connector loosening. Nevertheless, the technical and economic risk calculations shown remain valid for helping with the best decision making regarding the maintenance scheduling and, to refine them, one may use different models (eg, that describe the loosening mechanisms). By showing how to use a relatively inexpensive technique (thermography), quantifying the data uncertainty by robust methods, calculating the loss of life of an electrical component and enabling the upfront determination of the best time for an intervention, this study values engineering as an essential tool for the management of assets, by offering managers the confidence they need to make better decisions, based on evidence.